Exploring attacks in the NFT gaming industry: A study of risks and mitigation strategies - Mohima, Zarin Rahman; Bin Bashar, Syed Ziaul; Muktadir, Rawnak; Hossain, Amirah; Mahmud, Shafin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.